Pemberian Restitusi Terhadap Korban Tindak Pidana Perdagangan Orang dalam Undang-undang Nomor 21 Tahun 2007 Tentang Pemberantasan Tindak Pidana Perdagangan Orang - Hoshi Rahma Saraswati (Journal Law and Government, 2025)
This study focuses on answering two questions, namely: first, how restitution is provided to victims of human trafficking; and second, what are the advantages and disadvantages of Law No. 21 of 2007 on the Eradication of Human Trafficking in providing justice for victims. The research method used in this study is normative legal research, which focuses on the study of applicable positive legal norms. In this context, it refers to Law No. 21 of 2007 on the eradication of human trafficking. The results of this study are as follows: First, legal protection for victims of human trafficking is still inadequate and has not been implemented optimally. Although Law No. 21 of 2007 regulates the rights of victims, including the right to restitution, its implementation has not been effective. Many law enforcement officials do not understand the mechanism for providing restitution, while victims are often unaware of their rights. Therefore, it is necessary to establish specific regulations regarding restitution for victims of human trafficking, accompanied by an increased role for relevant institutions such as the Social Services Agency in assisting and rehabilitating victims. Second, weaknesses in the application of this law indicate the need for criminal law reform so that law enforcement can be more rigorous and fair. This reform is important to strengthen the protection of victims and ensure that their rights are fulfilled. Without reform, the objectives of the law to achieve justice, certainty, and benefit will not be realized, especially in ensuring justice for victims of human trafficking crimes.